China's energy consumption in the building sector: A Statistical Yearbook-Energy Balance Sheet based splitting method. (1st June 2018) - Huo, Tengfei; Ren, Hong; Zhang, Xiaoling; Cai, Weiguang; Feng, Wei; Zhou, Nan; Wang, Xia
Abstract: China's energy consumption in the building sector (BEC) is not counted as a separate type of energy consumption, but divided and mixed in other sectors in China's statistical system. This led to the lack of historical data on China's BEC. Moreover, previous researches' shortages such as unsystematic research on BEC, various estimation methods with complex calculation process, and difficulties in data acquisition resulted in "heterogeneous" of current BEC in China. Aiming to these deficiencies, this study proposes a set of China building energy consumption calculation method (CBECM) by splitting out the building related energy consumption mixed in other sectors in the composition of China Statistical Yearbook-Energy Balance Sheet . Then, China's BEC from 2000 to 2014 are estimated using CBECM and compared with other studies. Results show that, from 2000 to 2014, China's BEC increased 1.7 times, rising from 301 to 814 million tons of standard coal consumed, with the BEC percentage of total energy consumption stayed relatively stable between 17.7% and 20.3%. By comparison, we find that our results are reliable and the CBECM has the following advantages over other methods: data source is authoritative, calculation process is concise, and it is easy to obtain time series data on BEC etc. The CBECM is particularly suitable for the provincial government to calculate the local BEC, even in the circumstance with statistical yearbook available only. Highlights: Proposed a China building energy consumption calculation method based on Statistical Yearbook . Estimated China's energy use in building sector from 2000 to 2014 using the CBECM. CBECM overcame previous studies' inconsistent data sources and complex estimation process. CBECM's advantages: authoritative data source, easy to obtain time series and concise calculation.